Pengaruh Independensi, Gaya Kepemimpinan, Komitmen Organisasi, Pemahaman Good Governance, dan Budaya Organisasi Terhadap Kinerja Auditor(Studi pada Auditor Pemerintah di BPKP Jawa Tengah) - Inayati, Intan, Dra. Rina Trisnawati, A.ka, M.Si, Ph.d (2016)
The study aimed to understand influence of independency, leadership style, organization commitment, comprehension of good governance, and organizational culture toward performance of government auditors. Population in this study is whole government auditors who work at BPKP of Central Java Representation Office. Sample obtaining method using convenience sampling. The number sample used in this study is 40 respondents which the data could be analyzed and processed. Data analysis of the study used multi-linear regression analysis by SPSS Windows Program version 17.0. The study is consisted of dependent and independent variables. The dependent variable is performance of government auditor, and the independent variables are independency, leadership style, organization commitment, comprehension of good governance and organizational culture. The result shows that independency, leadership style, organization commitment, comprehension of good governance and organizational culture has positive influence toward performance of government auditors. The simultaneous test results that independency, leadership style, organization commitment, comprehension of good governance and organizational culture variable have collectively positive influence towards performance of government auditors